Geographical Information System development for Licensing and Enforcement Department of MBSA (GIS-LED) using spatial data analysis / Muhammad Faizal Ismail - Ismail, Muhammad Faizal (2012)
This project aims to develop a Geographical Information System for Licensing and Enforcement Department (GIS-LED) of MBSA. The functionality of this system is to help the department monitor the information license registration and renewal for the enterprise signboard license, billboard license and bunting license in Shah Alam. The information on the license is basically a location based so an information system that based on geographical and location is needed. Geographical Information System (GIS) are software system that used for capturing, storing, managing and displaying spatial data. The ability of GIS to capture information such as the location of offenders, on to a GIS has important implications for the rapid and timely accumulation of spatial data and the conduct of the analysis. In order to develop the system, few analysis must been made using the spatial data analysis, and the system must integrate with spatial database management system. This thesis has four objectives that need to be achieved. The first objective is described the spatial data analysis used in developing GIS-LED. The second objective is identified the requirement in order to develop GIS-LED. The third and fourth objective is designed and demonstrates the design using a prototype of GIS-LED. The first objective is achieved through the description of GIS and spatial data analysis done in chapter literature review. Other objectives are achieved through interviewing the License and Enforcement Department and Information and Communication Technology Department. The result of the interview is been analyzed to obtain the requirement of the system development. The development of GIS-LED using spatial data analysis will assist the department of Licensing and Enforcement through the management and monitoring the license registration and renewal, and it also gives lots of benefit to the department.